2003
DOI: 10.1046/j.1365-246x.2003.01876.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of wave propagation in media with discrete distributions of fractures: effects of fracture sizes and spatial distributions

Abstract: SUMMARY We model seismic wave propagation in media with discrete distributions of fractures using the pseudospectral method. The implementation of fractures with a vanishing width in the 2‐D finite‐difference grids is done using an effective medium theory (that is, the Coates and Schoenberg method). Fractures are treated as highly compliant interfaces inside a solid rock mass. For the physical representation of the fractures the concept of linear slip deformation or the displacement discontinuity method is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 32 publications
0
65
0
2
Order By: Relevance
“…If, however, the fractures and fracture spacing are closer in size to the seismic wavelength, then the fractures will scatter the seismic energy causing a more complex seismic signature Nakagawa et al, 2003;Vlastos et al, 2003;Willis et al, 2004). These larger scale features are the major fracture corridors within a reservoir.…”
Section: Fracture Systems -Numerical Models and Analysis Methodsmentioning
confidence: 99%
“…If, however, the fractures and fracture spacing are closer in size to the seismic wavelength, then the fractures will scatter the seismic energy causing a more complex seismic signature Nakagawa et al, 2003;Vlastos et al, 2003;Willis et al, 2004). These larger scale features are the major fracture corridors within a reservoir.…”
Section: Fracture Systems -Numerical Models and Analysis Methodsmentioning
confidence: 99%
“…Some authors modeled cracks in indirect manners, such as thin layers of equivalent homogeneous anisotropic materials (Vlastos et al, 2003) or arrayed point sources (van Antwerpen et al, 2002). In contrast, Saenger et al (2000) modeled cracks as a thin inclusion with zero elastic constants and small mass density within the "rotated staggered grid" developed by them.…”
Section: Introductionmentioning
confidence: 99%
“…Pointer et al (1998) treated the set of fractures as if it was a single fracture and they were able to detect its shape and size studying diffraction in the Rayleigh regime. On the other hand, Vlastos et al (2003) and Murai (2007) showed that length and spatial distribution of fractures cannot be seen in the Rayleigh regime.…”
Section: Introductionmentioning
confidence: 99%